2017
DOI: 10.3389/fmicb.2017.00451
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence That Selenium-Yeast Improves Chicken Health and Modulates the Caecal Microbiota in the Context of Colonization by Campylobacter jejuni

Abstract: Faced with ever-increasing demand, the industrial production of food animals is under pressure to increase its production. In order to keep productivity, quality, and safety standards up while reducing the use of antibiotics, farmers are seeking new feed additives. In chicken production, one of these additives is selenium. This element is expected to confer some advantages in terms of animal health and productivity, but its impact on chicken intestinal microbiota as well as on the carriage of foodborne pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…The authors hypothesised that this large variability is due to the colonisation by bacteria originating from the wider environment rather than predominantly from maternally derived bacteria. Thibodeau et al (2017) examined the influence of selenium-yeast on chicken caecal microbiota in the context of colonisation by C. jejuni in two experimental replicates with two independent batches of chickens. They saw that bacterial community structure was significantly different between the experimental replicates and concluded that there is a need for true biological replication when studying the chicken intestinal microbiota, especially when the observed changes are subtle.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesised that this large variability is due to the colonisation by bacteria originating from the wider environment rather than predominantly from maternally derived bacteria. Thibodeau et al (2017) examined the influence of selenium-yeast on chicken caecal microbiota in the context of colonisation by C. jejuni in two experimental replicates with two independent batches of chickens. They saw that bacterial community structure was significantly different between the experimental replicates and concluded that there is a need for true biological replication when studying the chicken intestinal microbiota, especially when the observed changes are subtle.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of gut microbiota studies across different avian species showed that a large factor contributing to the observed variation in avian intestinal microbiota composition was the study itself ( Waite and Taylor, 2014 ). Within the same study, differences in intestinal microbiota composition may also occur across independent poultry trials, even when the research conditions are carefully controlled and intended to be similar across trials ( Stanley et al, 2013 ; Thibodeau et al, 2017 ). Comparison of the outcomes of microbiota studies might be hampered by differences in technical aspects, biological variation within and between hosts, and environmental factors ( Lozupone et al, 2013 ; Brooks et al, 2015 ; Laukens et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years several studies have employed 16S rRNA gene sequences to comprehensively document changes in the cecal microbiota that accompany Campylobacter-colonization of broilers. These studies have noted differences in the relative abundance of Bifidobacterium, Lactobacillaceae, Clostridium cluster XIVa and Mollicutes, with transient age related shifts in specific members of the Lachnospiraceae and Ruminococcaceae (Thibodeau et al, 2015(Thibodeau et al, , 2017Connerton et al, 2018;Richards et al, 2019a). As an extension of the outputs from these studies it was recognized that transitions in the cecal microbiota were evident between 14 and 18 days that coincide with the reduced availability of maternal antibodies, and represent a window of opportunity for the entry for bacteria to bloom and new intestinal microbes to become established that can affect changes in gut health (Awad et al, 2016;Connerton et al, 2018;Ijaz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%